Essential Tremor and Parkinson's Disease: Exploring the Relationship. (9th January 2019) - Tarakad, Arjun; Jankovic, Joseph
Background: There is longstanding controversy surrounding the possible link between essential tremor (ET) and Parkinson's disease (PD). Inconsistent and unreliable diagnostic criteria may in part account for some of the difficulties in defining the relationship between these two common movement disorders. Methods: References for this systematic review were identified using PubMed with the search terms "essential tremor" AND "Parkinson's disease" with articles published in English between 1960 and September 2018 included. Results: In this review we provide evidence that some patients diagnosed with ET have an increased risk of developing PD years or decades after onset of action tremor. There are several still unresolved questions about the link between the two disorders including lack of verifiable diagnostic criteria for the two disorders and marked overlap in phenomenology. Here we review clinical, epidemiologic, imaging, pathologic, and genetic studies that address the ET–PD relationship. Several lines of evidence support the association between ET and PD, including overlapping motor and non-motor features, relatively high prevalence of rapid eye movement sleep behavior disorder (26–43%) in ET patients, increased prevalence of PD in patients with longstanding antecedent ET, increased prevalence of ET in family members of patients with PD, and the presence of Lewy bodies in the brains of some ET patients (15–24%). Discussion: There is a substantial body of evidence supporting the association between ET and PD within at least a subset of patients, although the nature and possible pathogenic mechanisms of the relationship are not well understood.